Pengembangan Video Edukasi GDS untuk Penderita Diabetes Tipe II di Posyandu - Nabila Yumna Zhafira; Ridwan Setiawan (Politeknik Kesehatan Kemenkes Bandung, 2025)
Background: Diabetes mellitus (DM) is a global health problem with increasing prevalence, including in Indonesia. Timed blood sugar screening education is important for the prevention of complications. The development of ADDIE-based “VIP-GDS” video media is expected to increase understanding and compliance with routine checks, considering that videos are effective for adult education based on preliminary studies. The objective of developing Video Information Media for Random Blood Sugar Testing (VIP-GDS) for type II diabetes patients at the Cilame Village Community Health Center using the ADDIE model. Methods: This type of research uses the R&D method with the ADDIE model approach (Analyze, Design, Develop, Implement, Evaluate) with research subjects 43 DM patients at the Cilame Village Area Health Center, The data analysis used in this study is descriptive analysis.Results: shows that the target needs audiovisual media with important aspects such as visual, audio, quality, and duration. The media was declared very feasible, with a material feasibility score of 97.22% and media feasibility of 94.64%. Implementation was carried out with informed consent, pretest, intervention 3 times, posttest. Wilcoxon test analysis showed a significant difference in knowledge before and after the intervention (p < 0.05), namely 0.00 with an increase in knowledge of 51.88%. Conclusion: VIP-GDS media is very feasible as a medium for efforts to prevent DM complications and is proven to have an effect on increasing patient knowledge about GDS examination.